2020
DOI: 10.1056/nejmoa1916046
|View full text |Cite
|
Sign up to set email alerts
|

Triple Inhaled Therapy at Two Glucocorticoid Doses in Moderate-to-Very-Severe COPD

Abstract: BACKGROUND Triple fixed-dose regimens of an inhaled glucocorticoid, a long-acting muscarinic antagonist (LAMA), and a long-acting β 2-agonist (LABA) for chronic obstructive pulmonary disease (COPD) have been studied at single dose levels of inhaled glucocorticoid, but studies at two dose levels are lacking. METHODS In a 52-week, phase 3, randomized trial to evaluate the efficacy and safety of triple therapy at two dose levels of inhaled glucocorticoid in patients with moderate-tovery-severe COPD and at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
508
7
50

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(577 citation statements)
references
References 20 publications
12
508
7
50
Order By: Relevance
“…Many studies have shown that dual or triple therapy will produce a statistically significant improvement in FEV 1 and reduce the exacerbation risk compared among different groups. [35][36][37] Unfortunately, in our study, the lung function of FEV 1 /FVC, symptoms of dyspnea and exacerbations after 1-year of follow-up were not improved, even worse compared to the baseline. The FEV 1 and CAT scores were stable.…”
contrasting
confidence: 76%
“…Many studies have shown that dual or triple therapy will produce a statistically significant improvement in FEV 1 and reduce the exacerbation risk compared among different groups. [35][36][37] Unfortunately, in our study, the lung function of FEV 1 /FVC, symptoms of dyspnea and exacerbations after 1-year of follow-up were not improved, even worse compared to the baseline. The FEV 1 and CAT scores were stable.…”
contrasting
confidence: 76%
“…We cannot address the reasons why the different treatments might influence the rate of decline of FEV 1 , although as we illustrate, treatment reduces exacerbation rates, which are associated with lung function decline (8,31). Recent data have shown that maximizing the therapy that is usually given to patients with COPD and more severe disease and exacerbations can reduce the risk of these events and of dying (32,33); these findings are consistent with this complementary evidence from the published literature. This systematic review is useful because it addressed one single research question, used studies with a large number of patients, had a high-quality control of the primary outcome (FEV 1 ) and followed patients over a long enough period of time to provide an answer to the research question.…”
Section: Data For Individual Components Could Only Be Completed For Isupporting
confidence: 52%
“…This is supported by double-blind, randomized controlled trials that have shown benefits of triple therapy versus LAMA/LABA and ICS/LABA combination therapies in reducing exacerbation rates. [22][23][24][25] Additionally, all-cause mortality data from the ETHOS and IMPACT studies have shown a beneficial effect for triple therapy compared with LAMAs/LABAs. 22,25 Adherence levels in our study (as defined by PDC) were high, with adherent patients experiencing significantly increased exacerbation rates versus non-adherent patients.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Additionally, all-cause mortality data from the ETHOS and IMPACT studies have shown a beneficial effect for triple therapy compared with LAMAs/LABAs. 22,25 Adherence levels in our study (as defined by PDC) were high, with adherent patients experiencing significantly increased exacerbation rates versus non-adherent patients. This is to be expected, as patients are more likely to adhere to medication if they are experiencing exacerbations that are not under control.…”
Section: Discussionmentioning
confidence: 99%